It takes two: heritable male effects on reproductive timing but not clutch size in a wild bird population - Evans, S; Postma, E; Sheldon, B (Wiley, 2020)
Within‐population variation in the traits underpinning reproductive output has long been of central interest to biologists. Since they are strongly linked to lifetime reproductive success, these traits are expected to be subject to strong selection and, if heritable, to evolve. Despite the formation of durable pair bonds in many animal taxa, reproductive traits are often regarded as female‐specific, and estimates of quantitative genetic variation seldom consider a potential role for heritable male effects. Yet reliable estimates of such social genetic effects are important since they influence the amount of heritable variation available to selection. Based on a 52‐year study of a nestbox‐breeding great tit (Parus major) population, we apply ‘extended’ bivariate animal models in which the heritable effects of both sexes are modelled to assess the extent to which males contribute to heritable variation in seasonal reproductive timing (egg laying date) and clutch size, while accommodating the covariance between the two traits. Our analyses show that reproductive timing is a jointly expressed trait in this species, with (positively covarying) heritable variation for laydate being expressed in both members of a breeding pair, such that the total heritable variance is 50% larger than estimated by traditional models. This result was robust to explicit consideration of a potential male‐biased environmental confound arising through sexually dimorphic dispersal. In contrast to laydate, males’ contribution to heritable variation in clutch size was limited. Our study thus highlights the contrasting extent of social determination for two major components of annual reproductive success, and emphasises the need to consider the social context of what are often considered individual‐level traits.